Assessment of Phenotypic Diversity in Breeding Lines of Barley at Rampur, Chitwan - Ale, Pabitra; Adhikari, Aakash; Dhungana, Babita; Gautam, Jigyasha; Adhikari, Anup; Dhakal, Krishna Hari (International Journal of Environment, Agriculture and Biotechnology, 2022)
The experiment was conducted during winter at the research field of National Maize Research Program (NMRP), Rampur, Chitwan situated in the inner-terai region of Nepal. Field experiment was conducted in the Completely Randomized Block Design (CRBD) with three replications. Three blocks was made on the field as local control to obtain more accurate data. Each block contains 14 experimental units. The collected data was recorded, entered and tabulated in Microsoft Excel and then analyzed by using R-software. Analysis showed non-significant variation for number of heads per meter square and significant variation for all other remaining traits. CHZ-NP-108-OY (111DAS) showed highest days to maturity and B86019-1K-2K-0K3 showed lowest. Days to booting, heading and anthesis were found highest in variety Bonus (std. check) with 81 DAS, 88 DAS and 98 DAS, respectively. Likewise, total quantity of tillers and number of effective tillers were highest in variety B90K-090-0K (2.9 and 2.4 respectively) and lowest in B86019-1K-2K-0K3 (1.9) and B86099-50K (1.6) respectively. Plant height was highest in variety B90K-024-1-1-2-0K (107cm) and lowest in Xveola-15 (82cm). Xveola-38 showed highest result for seed length (11.2mm) and grain yield (1634 kg/ha). Correlation between most of the traits was significant. Plant height changed into vast and undoubtedly correlated with tiller range (0.3*), powerful tiller (0.44***), flag leaf width (0.41***) flag leaf period (0.35**). Grain yield in keeping with hectare changed into significantly and definitely correlated with days to maturity (0.07**), flag leaf width (0.41***) plant peak (0.45**) and grain yield according to spike (0.1**). B86019-1K-2K-0K3 showed better adaptability and results for phenotypic characters whereas Xveola-38 performed best for the yield and yield attributing traits. So these varieties have the possibilities and potential for further study in Rampur, Chitwan.